Implementation of A Learning Management System using Prompt Engineering Horizon Artificial Intelligence in State Senior High School 1 Siau Barat - Alfrits Patrick Gunde; Harrychoon Angmalisang; Hiskia Kamang Manggopa; Parabelem Tinno Dolf Rompas (JR Education, 2026)
Prompt in artificial intelligence is one of the terms in technology that is currently often discussed by academics, becoming a weapon in producing a digital work and has an important role in artificial intelligence. Prompt is a command spoken by humans to machines to produce digital work. In a broad view, prompt is the art of designing science and a compass to guide humans in using artificial intelligence. This study aims to maximize Prompt Engineering Horizon Artificial Intelligence to create a learning management system in SMA Negeri 1 Siau Barat. This study uses the method This study uses the Research and Development (R&D) method with the ADDIE development model. The application of the learning management system to Teachers and Students of SMA Negeri 1 Siau Barat is the result of this research, where the prompt is made into a programming language coding arrangement and becomes a neat and ready-to-use web-based learning management system application. The implementation of this application is new and the first for teachers and students of SMA Negeri 1 Siau Barat and has a positive impact on the understanding and use of technology. On the other hand, this system also allows teachers and students to use smartphones optimally in the school environment for learning.